2019
DOI: 10.1002/mgg3.894
|View full text |Cite
|
Sign up to set email alerts
|

Strong increase of leukocyte apha‐galactosidase A activity in two male patients with Fabry disease following oral chaperone therapy

Abstract: Background Fabry disease (OMIM 301500) is an X‐linked disorder caused by alpha‐galactosidase A (α‐Gal A) deficiency. The administration of a pharmacologic chaperone (migalastat) in Fabry patients with amenable mutations has been reported to improve or stabilize organ damages and reduce lyso‐Gb3 plasma level. An increase of α‐Gal A activity has been observed in vitro in cells expressing amenable GLA mutations when incubated with migalastat. The impact of the drug on α‐Gal A in vivo activity has been poorly stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The split between preclinical and clinical studies was equal. A summary of the included clinical studies for Fabry disease is shown in Table 2 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 ]. A summary of the preclinical studies is shown in the Supplementary Material (Table S2) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The split between preclinical and clinical studies was equal. A summary of the included clinical studies for Fabry disease is shown in Table 2 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 ]. A summary of the preclinical studies is shown in the Supplementary Material (Table S2) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, current research aims at finding and standardizing compounds and delivery means targeting as specifically as possible the pathogenic chaperone [82][83][84][85][86]. If the chaperonopathy is by defect, positive chaperonotherapy is indicated, consisting in chaperone gene or protein replacement, or the use of manufactured chaperoning structures [87][88][89]; or chaperone-protein functional boosting with chemical compounds, namely chemical chaperones similar to those utilized for restoring enzymatic activity in genetic enzymopathies [82,[90][91][92][93]. Other approaches include the use of harmless stressors to induce production of a chaperone responsive to them when it is below the physiological concentration; namely, in cases of chaperonopathy by defect of the quantitative type [94].…”
Section: Conclusion and Perspectives For The Futurementioning
confidence: 99%